Finding suitable feature extraction method for condition monitoring of electrical equipment - Karobi, Synthia Hossain; Rahman, Tahmidur; Khoshnabish, Md Shoaib; Dey, Swarup Kumar (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2021